Optimization of extraction conditions and antioxidant activity of Solanum lycocarpum fruits - Martins, Gilmarcio Zimmermann [UNESP]; Santos, Adriana Nogueira dos; Vilela, Marcos Vinicius Ribeiro [UNESP]; Ferreira, Mariana de Carvalho; Oliveira, Wanderley Pereira de; Moreira, Raquel Regina Duarte [UNESP] (Science Alert, 2013)
Antioxidants are substances that may protect cells from the damage caused by unstable molecules known as free radicals. The capacity of natural antioxidant from phytochemical has increase attention from researchers and public. However, the extraction process is affecting the activity and the bioavailability of bioactive compounds. The Solanum lycocarpum is a plant of the Brazilian “cerrado”, popularly used as a hypoglycemic, hypocholesterolemic and control of metabolic diseases. Its effects are attributed to the presence of several glycoalkaloids (solamargine, solasonina) and solasodine. Therefore, the purpose of this communication was, investigate the optimization of extraction condition and evaluation of antioxidant activity from fruits of Solanum lycocarpum. The extracts were obtained using different solvent systems, i.e., water, 50% ethanol, ethanol absolute and ethyl ether (1:10 and 1:20) and different extraction processes: maceration with constant agitation at room temperature, maceration with constant agitation and heating at 30°C and ultrasound. The extracts were characterized by the amount of material extracted (1, 6 and 24 h) and the action of antioxidant activity by DPPH method. The results showed that the polar solvent (50% ethanol) and extractive process maceration with agitation to ambient temperature showed higher contents of extractable of fruits of S. lycocarpum (3.4 g %) and also showed higher antioxidant activity (88.57±2.41% de inhibition). This action whether the presence of glycoalkaloids (solamargine, solasonine and solasodine) in fruits S. lycocarpum which are polar compounds and may explain this increased antioxidant action of this extract.